Introduction aux relations industrielles - Paquet, Renaud (Relations industrielles / Industrial Relations, 2004)
The article reviews the book, "introduction aux relations industrielles," edited by Jean Boivin.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z